Karakteristik Sosial Ekonomi Rumah Tangga dan Tingkat Ketahanan Pangan Rumah Tangga Petani di Kabupaten Barito Kuala - Muhammad Husaini (AGRIDES: Jurnal Agribisnis Perdesaan, 2012)
The farmer social economic characteristics are important to see farmer capacities  to fulfill household food. The research show that farmer social economic characteristic included productive age of farmer, low level of farmer education, small amount of familiy members (3-4 person per household), farm land ownership amount  0.927 ha per household, total asset ownership relatively small amount 400,000 rupiah, per household, and farmer  activities relatively high in farmer group.  Food security indexes, amounted  94% of farmers household in betwen categorized food insecurity and less than foody insecurity, 6% of farmers household in to food security. The social economic farmer characteristics included farmers education, total family number, total asset are were not significan and its contribution relatively small (less than 20%) to farmers household food securities.   Meanwhile farm land ownership and farmer activities in farmers group  were significan and its contribution relatively high (over than 20%) to farmers household food securities.